Chagatai language and periods of its development - Shadkam, Z; Bazarkulova, B K (Journal of Oriental Studies, 2016)
Recently with the support of our President a lot of information is gathered and a big sum of money is allocated in order to research our Kazakh people’s history with the program cultural heritage. Most of the facts that were unknown for Kazakh people were written in Chagatai language. In this article we will try to give information about the development of Chagatai language using Turk professor M.Argunshah’s work “Chagatai’s Turkish” which was written about Chagatai language. Because, as our ancestors spoke in this language from the middle ages to the beginning of XX century it is very important to learn from the original source of information instead of using translation in order to establish Kazakh national consciousness. Therefore, nowaday we believe that we should include Chagatai language as the obligatory subject to the professions like History, Kazakh Philology, Oriental Studies and Turkish Studies.